2000
DOI: 10.1253/jcj.64.309
|View full text |Cite
|
Sign up to set email alerts
|

Severe Thrombocytopenia Caused by Digitoxin Intoxication in a Patient With Heart Failure Associated With Sjögren’s Syndrome

Abstract: Congestive heart failure (CHF) related to Sjögren's syndrome is extremely rare. This report concerns a patient who presented with CHF and severe thrombocytopenia (5,000/microl). Serum concentrations of K, Mg and digitoxin were 3.2mmol/L, 1.4mg/L and 57.2ng/ml, respectively. Digitoxin intoxication was evident, seemingly evoked by hypokalemia, hypomagnesemia, hepatorenal dysfunction and hypothyroidism. The severe thrombocytopenia was considered to have been caused by this intoxication, as it disappeared soon aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In our series, the incidence of thrombocytopenia was 6.37% in congestive heart failure patients, similar to previous report. Most recently, Mondal et al (2017a,b) (Haro et al, 2000) reported that oxidative stress induced modulation of platelet integrin α2bβ3 expression and shedding may play a potential role in the platelet apoptosis, inducing thrombocytopenia and non-surgical bleeding among heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the incidence of thrombocytopenia was 6.37% in congestive heart failure patients, similar to previous report. Most recently, Mondal et al (2017a,b) (Haro et al, 2000) reported that oxidative stress induced modulation of platelet integrin α2bβ3 expression and shedding may play a potential role in the platelet apoptosis, inducing thrombocytopenia and non-surgical bleeding among heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of thrombocytopenia in SS is usually mild without need for treatment. There were two cases of pSS with severe thrombocytopenia with clinical significance [13,14], one was developed in pSS and the other was caused by digoxin intoxication in pSS and treated well with steroid and discontinuation of the drug.…”
Section: Discussionmentioning
confidence: 99%